2021
DOI: 10.1177/11206721211029473
|View full text |Cite
|
Sign up to set email alerts
|

Periocular apocrine adenocarcinoma presenting as an orbital mass: clinicopathological features and management in four patients

Abstract: Purpose: Apocrine adenocarcinoma is a cutaneous adnexal malignancy which can rarely arise from ocular structures. In this retrospective study, we report our experience with four patients who had primary periocular apocrine adenocarcinoma initially presenting with an orbital tumor. Methods: Data extracted included demographics, clinical, imaging, and histopathological features, and treatment outcomes. Results: The definitive diagnosis was established after an incisional biopsy in all cases. Two patients were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Gordon et al reported a clinical case of recurrent orbital hemangiopericytoma that was irradiated five times [28]. Apocrine adenocarcinoma is a cutaneous adnexal malignancy with a slow-growing but refractory nature, which rarely arises from ocular structures, and sometimes initially present with an orbital tumor [29]. Our case also initially showed an orbital tumor with invasion to the paranasal sinus.…”
Section: Orbital Cancermentioning
confidence: 57%
See 1 more Smart Citation
“…Gordon et al reported a clinical case of recurrent orbital hemangiopericytoma that was irradiated five times [28]. Apocrine adenocarcinoma is a cutaneous adnexal malignancy with a slow-growing but refractory nature, which rarely arises from ocular structures, and sometimes initially present with an orbital tumor [29]. Our case also initially showed an orbital tumor with invasion to the paranasal sinus.…”
Section: Orbital Cancermentioning
confidence: 57%
“…She is alive with a stable tumor 19.8 months after reirradiation. Differential diagnosis of periocular malignant fibrous histiocytoma is difficult from leiomyosarcoma, atypical fibroxanthoma, sarcomatoid carcinoma, and atypical fibroxanthoma [29]. The mainstay of treatment is complete surgical excision with wide margins, and histologic margin control should be considered in addition to adjuvant radiotherapy.…”
Section: Orbital Cancermentioning
confidence: 99%